Tax Avoidance: Does Tax-Specific Industry Expertise Make a Difference? - McGuire, Sean T.; Omer, Thomas C.; Wang, Dechun (The Accounting Review, 2012)
ABSTRACT This study investigates whether the tax-specific industry expertise of the external audit firm influences its clients' level of tax avoidance. Our results suggest that clients purchasing tax services from their external audit firm engage in greater tax avoidance when their external audit firm is a tax expert. Because the external audit firm potentially influences clients' tax avoidance activities via the provision of tax consulting services and the financial statement audit, we also examine whether the overall expertise (i.e., the combined tax and audit expertise) of the external audit firm is associated with tax avoidance. We find that the external audit firm's overall expertise is generally associated with greater tax avoidance, which suggests that overall experts are able to combine their audit and tax expertise to develop tax strategies that benefit clients from both a tax and financial statement perspective. In combination, our results suggest that the tax-specific industry expertise of the external audit firm plays a significant role in its clients' tax avoidance. Data Availability: Data used in this study are available from public sources identified in the article.